Divergent mortality patterns for second generation men of North-African and South-European origin in France: Role of labour force participation - Myriam Khlat; Matthew Wallace; Michel Guillot (Elsevier, 2019)
Introduction: In France, second generation men of South-European origin were recently found to experience a mortality advantage, as opposed to second generation men of North-African origin, subjected to a large amount of excess mortality. We analyze the roles of education and labor force participation in the explanation of these contrasting mortality patterns. Materials and methods: Our data consisted of a nationally-representative sample of individuals aged 18-64 years derived from the 1999 census, with mortality follow-up until 2010. Results: The two groups of second generation men, and particularly those of North-African origin, were less educated than the native-origin population, but only the latter was disadvantaged in terms of labor force participation. Relative to the native-origin population, the mortality hazard ratio for second generation men of North-African origin (HR = 1.71 [1.09-2.70]) remained significant after adjusting for level of educational attainment (HR = 1.59 [1.01-2.50]), but not after adjusting for economic activity (HR = 1.20 [0.76-1.89]) or for both variables (1.16 [0.74-1.83]). Conversely, the mortality hazard ratio for second generation men of South-European origin (HR = 0.64 [0.46-0.90]) remained unchanged after adjustment for level of educational attainment and/or economic activity. Conclusion: The findings shed light on the salient role of labor market disadvantage in the explanation of the mortality excess of second generation men of North-African origin in France, and on the favorable situation of second-generation men of South-European origin in terms of labour market position and mortality. The theoretical and policy implications of the findings are discussed. Keywords: Migrants, Second generation, Mortality, Education, Labor force participation